“Motorosis”, the latest convinience and laziness sickness (Fiep Bulletin - online, 2015)
As war stated on the pages of the FIEP – Bulletin no. 2/1955, Presidente Eisenhower had ealled a conference for the 27th Setember, 1955 to discuss the physical training of American youth. It was postponed, however, on account of his heart-attack, which occurred three days before the conference.